Monetary Policy Dynamics and the Nigeria’s Global Competitiveness: The Missing Link - Agbogun, Oghenekparobo Ernest; Oshiobugie, Omolegie Bruno; Oboro, Oghenero Godday (Journal of Business Management and Economic Development, 2024)
Despite the series of monetary policies adopted by the Nigerian government over time, the (Nigerian) economy in comparison to other countries in the world like South Africa, the USA, Ghana, and the like is still improvised. Still, inconsistency between monetary policy formulation and implementation remains another major issues yet unattended to. It is in this regards that, the current study is dedicated towards examining the effect of monetary policy dynamics and the Nigeria’s global competitiveness from 1992 to 2021 (i.e., 30 years) using Autoregressive Distributed Lag (ARDL) model. The study disclosed that, the variables are integrated at level and first difference while the ARDL Bound test evidenced that, the series cointegrates. Specifically, monetary policy rate has a positive minimal effect on Nigeria’s global competitiveness, while the CRR improved Nigeria’s global competitiveness significantly. However, both lending rates and exchange rates have a significant negative effect on economic competitiveness. Consequently, the paper concludes that both the cash reserve ratio and the Nigeria’s demeaning state are attributed to the high exchange rate (EXR) and high lending rates. Thus, the paper submits that the current monetary policy rates are sustained and that all DMBS should adhere to the stipulated Cash Reserve Ratio (CRR) since it has improved the Nigeria’s global competitiveness significantly. Lastly, the study confirmed that, the missing link is the policy surmount on the part of the Nigerian government.